Jawetz, Melnick, & Adelberg's medical microbiology - Carroll, Karen C. (McGraw-Hill Education, 2016)
This book delivers a concise, up-to-date overview of the roles microorganisms play in human health and illness. The book also includes an entire chapter of case studies that focuses on differential diagnosis and management of microbial infections.